A radical history of the world - Faulkner, Neil (London : Pluto Press, 2018)
Offers a historical study of the world that contends that history is continually created and recreated by conscious, collective human action. Faulkner argues that the struggles of the common people--slaves, serfs, handloom weavers, mine workers, women fighting oppression, black people fighting racism, colonized people fighting imperialism--these struggles, occasionally fusing into mass revolutionary upsurges, drive the historical process. He states that this is an approach to history that emphasizes agency, contingency, and the existence of alternatives; an approach that rejects the view that war and empire are inevitable, that there is no alternative to the market, and that greed, bullying, and violence are universal. In other words, Faulkner contends that the course of history is not predetermined, its outcome is not inevitable; it can go in different directions according to what human beings do.
Hunters and farmers, c. 7 million-3000 BC -- The first class societies, c. 3000-1000 BC -- Ancient empires, c. 1000-30 BC -- The end of antiquity, c. 30 BC-AD 650 -- The medieval world, c. AD 650-1500 -- European feudalism, c. AD 650-1500 -- The first wave of bourgeois revolutions, 1517-1660 -- Absolutist Europe and capitalist globalisation, 1660-1775 -- The second wave of bourgeois revolutions, 1775-1815 -- The rise of industrial capitalism, c. 1750-1850 -- The age of blood and iron, 1848-1873 -- Imperialism and war, 1873-1918 -- The revolutionary wave, 1917-1928 -- The Great Depression and the rise of fascism, 1929-1939 -- World War and Cold War, 1939-1967 -- The world on fire, 1968-1975 -- The new world disorder, 1975-2008 -- Capitalism's greatest crisis? The early twenty-first century -- Conclusion: Making the future -- Timeline -- Sources -- Bibliographical notes -- Select bibliography -- Index.
"A radical history of the world draws on text originally published in A Marxist history of the world (Pluto Press, 2013)."--Title page verso.
Includes bibliographical references (pages 546-555) and index.
ENH
Trim Education
Keywords: Historical materialism; Marxian historiography; World history